(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Philippines has been facing a problem on the preservation of her folklores which reflects the culture and tradition of the Filipino and thus putting the national identity at the brink of collapse. In this connection, this study aims to provide enlightenment on the social realities found in Philippine folklore and paves way to the enrichment of the country’s cultural heritage and the upholding of the national identity. This study analyzes the socio-cultural religiousity reflected in Guindulmanon Folklore of Guindulman, Bohol focusing on the themes, archetypes of the textual narratives which depict the socio-religious consciousness of the Guindulmanons. The verbal data supporting this assumption is analyzed through qualitative analysis using the theories of mimesis and Jung’s archetypal theory. This reveals that the people of Guindulman, Bohol have rich folklore about the existence of engkanto in their community. The dominant themes of the folklore deal with the belief on the existence of engkanto which induces advantageous fear to be people. The folklore also present archetypes which compile the beliefs of the people on the ways engkanto imitate, inflict, enchant humans and how they interact with them in the society. The folklore divulge that Guindulmanons are greatly affected with their primordial beliefs and practices leading them to have split-level of Christianity. In conclusion, the folklore reveal that Guindulmanons have the collective fear leads to the upholding of the importance of virtues such as vigilance, respectfulness, faith in God, trustfulness and discernment in order to establish to peaceful living.